The behaviour of Alcaligenes denitrificans in different respiratory conditions : effect of C/N ratio and P concentration - Teixeira, P. (2001)
In order to improve the rate of denitrification by Alcaligenes denitrificans the effect of phosphorous concentration and the carbon /nitrogen ratio, under aerobic and anoxic conditions, were studied. Batch experiments were conducted under anoxic and aerobic conditions, with two different carbon/nitrogen ratios (C/N = 2 and C/N = 3) and with three different phosphorous concentrations (P = 2 mg/l, P = 20 mg/l and P = 200 mg/l). In anoxic conditions, in all the experiments, Alcaligenes denitrificans showed a typical diauxic growth. The specific consumption rate of nitrate was very similar for both C/N ratios and for the three phosphorous concentrations studied. The consumption of citrate was almost the same for both C/N ratios, but increased with increasing phosphorous concentration. Moreover, for C/N = 2 citrate was completely consumed, while for C/N = 3, only about half of its concentration was consumed. This reveals that a C/N = 3 is too high. In aerobic conditions, for both C/N ratios, citrate was always totally consumed while only a small amount of nitrate was consumed. Besides, there was no nitrite production. So, it seems evident that, in aerobic conditions, the substrates were only consumed for cell synthesis and no significant denitrification was observed.